2011
DOI: 10.1371/journal.pone.0020945
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Prevents Dopaminergic Neurodegeneration in Experimental Parkinsonian Models: The Association with Anti-Inflammatory Responses

Abstract: BackgroundIn addition to their original applications to lowering cholesterol, statins display multiple neuroprotective effects. N-methyl-D-aspartate (NMDA) receptors interact closely with the dopaminergic system and are strongly implicated in therapeutic paradigms of Parkinson's disease (PD). This study aims to investigate how simvastatin impacts on experimental parkinsonian models via regulating NMDA receptors.Methodology/Principal FindingsRegional changes in NMDA receptors in the rat brain and anxiolytic-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 82 publications
2
78
0
1
Order By: Relevance
“…Our studies and Selley (Selley, 2005;Wang et al, 2005) have shown that simvastatin regulated dopaminergic systems including receptors and transmission in the brain. Also, our study found the alterations of NMDA and M1/4 receptors in the brains following simvastatin treatment Wang et al, 2009b;Yan et al, 2011). Whether the application of simvastatin in Parkinsonian rats also influences the expression of M1 receptors raises an interesting question.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…Our studies and Selley (Selley, 2005;Wang et al, 2005) have shown that simvastatin regulated dopaminergic systems including receptors and transmission in the brain. Also, our study found the alterations of NMDA and M1/4 receptors in the brains following simvastatin treatment Wang et al, 2009b;Yan et al, 2011). Whether the application of simvastatin in Parkinsonian rats also influences the expression of M1 receptors raises an interesting question.…”
Section: Introductionmentioning
confidence: 56%
“…TH staining was performed as described in Yuan's study (Yuan et al, 2005;Yan et al, 2011). Briefly, distilled water was used to wash the brain sections for three times (5 min/per time), and the sections were immerged in citrate buffer for 20 minutes.…”
Section: Tyrosine Hydroxylase Immunohistochemistry Stainingmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well documented that NMDA receptors in the brain have a close correlation with anxiety-like activity (Bergink, van Megen, Westenberg, 2004;ChojnackaWójcik, Kłodzinska, Pilc, 2001). Modulation of NMDA receptors activity after SIM treatment could explain the drug's anxiolytic-like effects (Camargo et al, 2013;Carrocini et al, 2012;Cruz et al, 2011;Kilic et al, 2012;Pauleti et al, 2013;Santos et al, 2012;Wang et al, 2009;Yan et al, 2011). This hypothesis could be supported by the fact that altered levels of NMDA receptors in the hippocampus and amygdala directly influence anxiety behaviors (Barkus et al, 2010;Blundell, Adamec, 2007;Masneuf et al, 2014).…”
Section: Introductionmentioning
confidence: 98%